Uma análise do direito e da democracia na perspectiva da teoria do discurso de Habermas - Silva, Eder Mauro da (Universidade Federal de São Carlos, 2018)
This dissertation intends to reflect on some points of the reconstructive analysis of law and democracy in the perspective of Habermas' discourse theory, in order to discuss the possibility of an emancipatory social integration inscribed in modern society. Starting from the communicative rationality, the public sphere category and the tension between facticity and validity, present in different forms and at various moments in the work Between Facts and Norms, our work reflects on the communicative potentials inserted in modern institutions. Positive law, in the tense relation of distinct and complementary to morality, is the "transforming" element that allows us to move both in the world of life and in the system, allowing us, within the democratic process, to think about the elaboration and implementation of the association of free and equal citizens. The procedural model of democracy proposed by Habermas, understood as a dynamic process, devoid of content, will constitute the point of balance between the demands of communicative action, filtered by the public sphere, and the decision-making processes of the political system. In this sense, our work, in view of emancipation, discusses the emergence of a radical reflection on the legitimacy of law and democracy as fundamental categories of social integration facing the challenges of complex capitalist and pluralistic modernity.
Keywords: Integração social; Emancipação; Teoria do discurso; Direito; Democracia; Social integration; Emancipation; Discourse theory; Law; Democracy; CIENCIAS HUMANAS::FILOSOFIA::ETICA